COVID-19 and women's intersectionalities in Africa - Johnson, Adetokunbo; Budoo-Scholtz, Ashwanee (Pretoria University Law Press (PULP), 2023)
About the publication COVID-19 has become one of the most severe issues dominating discussions on the agendas of states globally, and across the African continent, since its emergence in 2019. The COVID-19 pandemic has regrettably brought into sharp focus the continued multiple and intersecting forms of discrimination faced by women and girls in Africa because of their intersecting identities. Yet, paradoxically, although African women are disproportionately affected by the crisis, they are largely invisible in the responses. Several African states and governments have taken different policy measures in response to the pandemic. These responses have taken different dimensions, including shutting down economies, imposition of lockdowns, coercive quarantine measures with police enforcement and criminal consequences for offenders violating these rules. Unfortunately, these responses have reinforced and amplified women's disproportionate disadvantage and gender inequalities in Africa. Against this backdrop, this book asks the intersectional question about women's experiences during the COVID-19 pandemic in Africa. Applying an intersectional human rights lens involves questioning how the intersecting identities that African women embody affect their experiences of the COVID-19 pandemic.